Dynamics of Xanthomonas oryzae pv. oryzae populations in Korea and their relationship to known bacterial blight resistance genes - Jeung, J.U.; Heu, S.G.; Shin, M.S.; Vera Cruz, C.M.; Jena, K.K. (Scientific Societies, 2006)
Developing resistant cultivars requires an understanding of the dynamics of the pathogen populations as well as the genetics of host resistance. Bacterial leaf blight (BB), caused by the vascular pathogen Xanthomonas oryzae pv. oryzae, has become one of the most devastating diseases of rice. We demonstrate here the quantitative analyses of responses of near-isogenic lines carrying various BB resistance (R) genes and R-gene combinations against 16 X. oryzae pv. oryzae isolates representing Korean BB pathotypes. The estimated main effects of each R gene against the 16 isolates identified prominent differences in BB pathotypes between Korea and other countries. Three major aspects of our quantitative observations and statistical analysis are (i) strong and broad resistance of xa5; (ii) independent and additive genetic actions of Xa4, xa5, and Xa21 under digenic or trigenic status; and (iii) a strong quantitative complementation effect contributed by the functional alleles of Xa4 and Xa21. We conclude that the pyramid line containing genes Xa4, xa5, and Xa21 would be the most promising and valuable genotype for improving Korean japonica cultivars for BB resistance.